"These things are dangerous": Understanding induced abortion trajectories in urban Zambia. (March 2016) - Coast, Ernestina; Murray, Susan F.
Abstract: Unsafe abortion is a significant but preventable cause of global maternal mortality and morbidity. Zambia has among the most liberal abortion laws in sub-Saharan Africa, however this alone does not guarantee access to safe abortion, and 30% of maternal mortality is attributable to unsafe procedures. Too little is known about the pathways women take to reach abortion services in such resource-poor settings, or what informs care-seeking behaviours, barriers and delays. In-depth qualitative interviews were conducted in 2013 with 112 women who accessed abortion-related care in a Lusaka tertiary government hospital at some point in their pathway. The sample included women seeking safe abortion and also those receiving hospital care following unsafe abortion. We identified a typology of three care-seeking trajectories that ended in the use of hospital services: clinical abortion induced in hospital; clinical abortion initiated elsewhere, with post-abortion care in hospital; and non-clinical abortion initiated elsewhere, with post-abortion care in hospital. Framework analyses of 70 transcripts showed that trajectories to a termination of an unwanted pregnancy can be complex and iterative. Individuals may navigate private and public formal healthcare systems and consult unqualified providers, often trying multiple strategies. We found four major influences on which trajectory a woman followed, as well as the complexity and timing of her trajectory: i) the advice of trusted others ii) perceptions of risk iii) delays in care-seeking and receipt of services and iv) economic cost. Even though abortion is legal in Zambia, girls and women still take significant risks to terminate unwanted pregnancies. Levels of awareness about the legality of abortion and its provision remain low even in urban Zambia, especially among adolescents. Unofficial payments required by some providers can be a major barrier to safe care. Timely access to safe abortion services depends on chance rather than informed exercise of entitlement. Highlights: Despite legal provision in Zambia, not all urban women access abortions safely. Unofficial payments requested by some providers cause delay and deter use. Self-administered medical abortion may now be a widespread strategy. Accessible information about how to obtain safe abortion is needed in Zambia.